2018
DOI: 10.2118/194006-pa
|View full text |Cite
|
Sign up to set email alerts
|

Crude-Oil/Brine Interaction as a Recovery Mechanism for Low-Salinity Waterflooding of Carbonate Reservoirs

Abstract: Summary Low-salinity waterflooding in limestone formations has been less explored and hence less understood in enhanced-oil-recovery (EOR) literature. The mechanisms leading to improved recovery have been mostly attributed to wettability alteration, with less attention given to fluid/fluid-interaction mechanisms. In this work, we present a thorough investigation of the formation of water-in-oil microdispersions generated when low-salinity brine encounters crude oil and the suppressed snap-off ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 17 publications
6
28
0
Order By: Relevance
“…The possible role of crude oil and fluid–fluid interactions during LSWI in carbonate and sandstone reservoirs had been underestimated until microdispersion formation was introduced as the main responsible mechanism of LSWI . The microdispersion theory could support the extra oil recovery during LSWI regardless of rock type, which was a remarkable discovery for the oil and gas industry. , It was shown that microdispersions were water clusters surrounded with oil surface-active materials leading to wettability alteration through the detachment of surface-active materials from the rock surface; this work was also supported by other researchers. , Several studies have been published in the literature reporting the formation of water microdispersion as the main mechanism of LSWI irrespective of different terminologies. , Other mechanisms were also introduced to attribute the additional oil recovery during LSWI to the fluid–fluid interaction, such as interfacial viscoelasticity variations and osmotic effects . Alvarado et al suggested that either increasing the sulfate content or decreasing the salinity of injection water would lead to incremental oil recovery through increasing the interfacial viscoelasticity.…”
Section: Introductionmentioning
confidence: 59%
“…The possible role of crude oil and fluid–fluid interactions during LSWI in carbonate and sandstone reservoirs had been underestimated until microdispersion formation was introduced as the main responsible mechanism of LSWI . The microdispersion theory could support the extra oil recovery during LSWI regardless of rock type, which was a remarkable discovery for the oil and gas industry. , It was shown that microdispersions were water clusters surrounded with oil surface-active materials leading to wettability alteration through the detachment of surface-active materials from the rock surface; this work was also supported by other researchers. , Several studies have been published in the literature reporting the formation of water microdispersion as the main mechanism of LSWI irrespective of different terminologies. , Other mechanisms were also introduced to attribute the additional oil recovery during LSWI to the fluid–fluid interaction, such as interfacial viscoelasticity variations and osmotic effects . Alvarado et al suggested that either increasing the sulfate content or decreasing the salinity of injection water would lead to incremental oil recovery through increasing the interfacial viscoelasticity.…”
Section: Introductionmentioning
confidence: 59%
“…EDX analysis together with XRD data for the Indiana limestone indicated a more than 99% CaCO 3 composition representing different forms of calcite. The XRD data peaks were presented in our previous publication . The absence of clay and anhydrite in the limestone sample helps study wettability alteration mechanisms solely associated to calcite mineral serving as a good proxy to limestone formations .…”
Section: Methodsmentioning
confidence: 99%
“…Calcite dissolution was observed by Mahani et al, explaining that such an observation could only be a secondary trigger to carbonate rock wettability alteration because the wettability alteration was still observed in the absence of calcite dissolution . Other proposed mechanisms for the observed IOR in carbonate rocks include formation of water-in-oil microdispersions, , suppression of the snap-off effect, and osmosis, which are all related to the interactions at the oil–brine interface.…”
Section: Introductionmentioning
confidence: 97%
“…On the basis of these characteristics of surfactants, LSW disperses into oil that contains a considerable amount of surfactants as a microemulsion and replaces trapped oil from water-wet or mixed-wet reservoirs through micromodel experiments . Moreover, it has been reported that microdispersion of water is induced by the variation in the ion compositions of water surrounding oil based on experimental results obtained through visualization and element mapping with energy-dispersive X-ray spectrometry (EDX) and environmental scanning electron microscopy (E-SEM) . In addition, larger scale emulsions affect the flow path.…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, it has been reported that microdispersion of water is induced by the variation in the ion compositions of water surrounding oil based on experimental results obtained through visualization and element mapping with energydispersive X-ray spectrometry (EDX) and environmental scanning electron microscopy (E-SEM). 12 In addition, larger scale emulsions affect the flow path. For example, the role of mobilized clay particles has been considered as an emulsifier 13,14 In this study, we investigated the EOR mechanism of LSWF focusing on the oil/water interaction by targeting a specific offshore oil reservoir.…”
Section: Introductionmentioning
confidence: 99%